2020
DOI: 10.1097/icl.0000000000000699
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Administration of 0.02% Atropine and Orthokeratology for Myopia Control

Abstract: Objective: To compare the efficacies of 0.02% atropine eye drops and orthokeratology to control axial length (AL) elongation in children with myopia. Methods: In this historical control study, 247 children with myopia whose administration of 0.02% atropine (n=142) or underwent orthokeratology from an earlier study (n=105, control group) were enrolled. Data on AL and other baseline parameters were recorded at baseline and after 1 and 2 years of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…We found that OK lenses were more effective than 0.01% atropine in controlling AL elongation in high myopic eyes but not in low myopic eyes in children with anisometropia. This is consistent with Lin et al 17 and Lyu et al 18 who reported that OK lenses provide a better outcome compared with administration of 0.125% and 0.02% atropine for controlling AL elongation in children with high myopia. This could be explained by the above-mentioned peripheral myopic defocus hypothesis when wearing OK lens.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that OK lenses were more effective than 0.01% atropine in controlling AL elongation in high myopic eyes but not in low myopic eyes in children with anisometropia. This is consistent with Lin et al 17 and Lyu et al 18 who reported that OK lenses provide a better outcome compared with administration of 0.125% and 0.02% atropine for controlling AL elongation in children with high myopia. This could be explained by the above-mentioned peripheral myopic defocus hypothesis when wearing OK lens.…”
Section: Discussionsupporting
confidence: 91%
“…Sample size was calculated based on the results from previous studies. 17,18 We assumed that 90% power was desired to detect at least 0.14-mm AL difference between OK lenses and 0.01% atro-pine groups, with significance at the 2-sided 5% level and a referred SD of 0.20. Thus, this study required 43 participants in each group.…”
Section: Methodsmentioning
confidence: 99%
“…0.01% atropine was self-prepared in all studies. In the Yong Lyu study [21] , the 0.02% atropine eye drops were made by diluting 1% atropine with saline. The 0.125% atropine used in Ren 2017 [20] study was the lowest concentration of atropine available on the market.…”
Section: Literature Search and Characteristics Of Included Studiesmentioning
confidence: 99%
“…[16][17] At present, there are some literature reports on the comparative study of atropine and ortho-k single treatment for juvenile myopia, but results are still controversial. [18]- [21] Due to the different mechanism of atropine and ortho-k in controlling myopia, the combination of atropine and ortho-k may produce additive effect. Considering adverse effects and rebound reactions of different doses of atropine, several studies con rmed that the combination of 0.01% atropine and ortho-k is more effective than ortho-k alone in slowing down the axial elongation of myopia children.…”
Section: Objectivementioning
confidence: 99%
“…Although a concentration-dependent response seems reasonable [ 20 ], these data (a non-significant slowing of axial elongation for 0.01% atropine over 24 months) contradict previous studies and only reflect experience over two years. While other physicians have tested the daily use of a 0.02% concentration [ 21 ], 0.01% atropine is currently the most commonly used and investigated agent in the United States, East Asia, and Europe [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%